Constraining or Enabling Green Capability Development? How Policy Uncertainty Affects Organizational Responses to Flexible Environmental Regulations. (6th September 2016) - Teeter, Preston; Sandberg, Jörgen
Abstract: Despite their growing popularity, flexible environmental regulations are increasingly characterized by high levels of policy uncertainty. This uncertainty poses numerous challenges for managers, policymakers and researchers, for we still have a poor understanding of how such uncertainty affects organizational responses and the ability of organizations to generate unique capabilities. This paper presents findings of a qualitative study of how organizations respond to the introduction of flexible environmental regulations amidst extremely high levels of policy uncertainty. Through an investigation of Australia's complex, and ultimately brief, carbon pricing scheme, we find that policy uncertainty forces organizations to focus their responses on short‐term investments and dealing with that very uncertainty, thereby precluding the development of green capabilities and preventing flexible regulations from achieving their intended policy results. However, we also find that organizations are able to develop innovative regulatory coping capabilities and that variation in regulatory response results in a variation in these capabilities.